2021
DOI: 10.3389/fpsyg.2021.612792
|View full text |Cite
|
Sign up to set email alerts
|

Perceived vs. Actual Emotion Reactivity and Regulation in Individuals With and Without a History of NSSI

Abstract: Non-suicidal self-injury (NSSI) has consistently been associated with self-reported difficulties in emotion reactivity and the regulation of negative emotions; however, less is known about the accuracy of these self-reports or the reactivity and regulation of positive emotions. The present study sought to investigate differences between women with and without a history of NSSI on: (a) self-reported general tendencies of negative and positive emotion reactivity, (b) self-reported general tendencies of negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…In terms of recovery from negative mood, counter to our predictions we found no evidence that young adults with a recent history of NSSI recovered less effectively from emotional challenge compared to controls. In a similar manner, young adults who had engaged in NSSI in the past two years and those without a history of NSSI showed similar subjective recovery from a sad film clip (Mettler et al, 2021). In contrast to both Study 2 and…”
Section: Subjective Responding To Acute Stressmentioning
confidence: 67%
See 4 more Smart Citations
“…In terms of recovery from negative mood, counter to our predictions we found no evidence that young adults with a recent history of NSSI recovered less effectively from emotional challenge compared to controls. In a similar manner, young adults who had engaged in NSSI in the past two years and those without a history of NSSI showed similar subjective recovery from a sad film clip (Mettler et al, 2021). In contrast to both Study 2 and…”
Section: Subjective Responding To Acute Stressmentioning
confidence: 67%
“…Two studies have found that, compared to people with no history of self-injury, people who selfinjure experienced greater negative mood reactivity to conflict discussions (Kaufman et al, 2019), and, for people with both NSSI and BPD, imagined social rejection (Gratz et al, 2019). In contrast, other studies have found no difference in how people with and without a history of self-injury subjectively respond to anger inductions (Weinberg & Klonsky, 2012), sad film clips (Davis et al, 2014;Mettler et al, 2021), acute social stress (Kaess et al, 2012), personally-relevent social distress or criticism scripts (Allen et al, 2019;Gratz et al, , 2019, or social exclusion paradigms (Groschwitz et al, 2016;Schatten et al, 2015). Still other studies have reported that, compared to people with no history of self-injury, people who self-injure show reduced subjective reactivity when writing about a personal failure (Bresin & Gordon, 2013) or watching a sad film clip (Boyes et al, 2020).…”
Section: Capturing Multi-channel Emotional Responding In Real-timementioning
confidence: 82%
See 3 more Smart Citations